Communicating with XML - Salminen, Airi; Tompa, Frank (Springer Science+Business Media, LLC, 2011)
This book provides extensive insight into the possibilities and challenges of XML in building new information management solutions in networked organizations. Applications across a broad spectrum are examined and numerous case studies are presented